Radiation exposure in interventional cardiology: relationship between patient radiation dose, demographic characteristics and procedural factors. (25th November 2020) - McCaughey, C; Kumar, R; Kumar, J; Matiullah, S
Abstract: Introduction: There has been a significant increase in Interventional Cardiology (IC) procedures over last few decades across the globe. The introduction of newer techniques and procedure types in IC has contributed to an overall increase in radiation exposure to both operators and patients alike. Unlike diagnostic imaging, IC procedures are heterogeneous and vary in their complexity based on a myriad of factors, such as patient disease characteristics, anatomy, nature of lesions and operator technique. Purpose: The aim of the study is to evaluate the demographic and procedural characteristics associated with increased radiation dose. Limited studies exist on the impact of demographic and procedural characteristics on cumulative radiation dose. Methods: Single-centre retrospective observational study of elective Percutaneous Coronary Intervention (PCI) patients from October 2018 to December 2018 in a 24/7 Irish pPCI centre. Patient level data including weight, height, demographic and procedural characteristics were collected for 65 consecutive elective PCI cases. Radiation exposure metrics, including Kerma Area Product (Pka), Reference Air Kerma (Ka, r) and Fluoroscopy Time (FT), were also collected. A Mann-Whitney U Test was used to assess for differences in radiation exposure between groups and a multivariate regression analysis was performed in order to identify those variables which contributed to radiation exposure. Results: Median total radiation exposure for our cohort was (Q1–3) -Pka 109 (61–154) Gy·cm 2, Ka, r 1746 (1, 082–2, 530)mGy and FT 16 (10–25)mins. Males (n=48) had a significantly higher radiation exposure Pka 126 (84–171) vs 56 (27–114)Gy·cm 2 p=0.001; Ka, r 2094 (1256–2936) mGy p=0.006) than females. Those who underwent femoral access had significantly lower radiation exposure (Pka 50 (38–77) vs 114 (63–158) Gy·cm 2 p=0.019; Ka, r (897 (725–1094) vs 2020 (1092–2618) mGy; p=0.018) when compared to radial access. Increasing body mass index (BMI) (p=0.03), multi vessel PCI (p=0.001) and the use of a "sheathless" technique (p=0.029) were associated with increasing radiation exposure (r 2 =0.630 Pka; Ka, r r 2 =0.611). Stent characteristics and all other clinical risk factors (HTN, smoking, DM, renal impairment, previous PCI) had no significant impact on radiation exposure. Conclusion: Radiation exposure during IC in our cohort was within the range of most European Diagnostic Reference Levels (DRL's). Increased BMI and male gender were associated with increased radiation exposure. Procedural characteristics such as radial access, multi vessel PCI and the use of sheathless technique were independently associated with increasing radiation exposure. We recommend dose documentation of all procedures for these patients to avoid radiation hazards; with periodic assessment of statistical dose recording and planned follow up. Funding Acknowledgement: Type of funding source: None